PARENTING PATTERNS FOR CHILDREN OF CRIMINAL OFFENDERS - Fabira, Dwie Shafa; Muhammad, Ali (PT Altin Riset Publishing, 2024)
This study aims to identify the parenting styles applied to juvenile offenders in Indonesia, analyze the social, economic, and cultural factors influencing these parenting styles, and explain the relationship between parenting styles and children's tendencies to commit crimes. This research employs a qualitative method with a case study approach. Data collection was conducted through in-depth interviews, observations, and documentation from several families with juvenile offenders. Data analysis was performed using a descriptive qualitative approach to reveal patterns and relationships among variables. The findings indicate that authoritarian and permissive parenting styles dominate among families of juvenile offenders. The authoritarian parenting style, characterized by strict control and a lack of affection, contributes to aggressive behavior and a tendency to rebel. In contrast, the permissive parenting style, which grants excessive freedom to children, tends to result in uncontrolled behavior and rule-breaking. Socio-economic factors, such as financial pressures, as well as cultural values, also influence these suboptimal parenting styles. This study concludes that there is a need for intervention in the form of parenting education programs and social support for vulnerable families to prevent children's involvement in criminal activities.